Importance of Monetary Policy in the Economic Development Process - Acharya, Subash (Socio-Economic Development Panorama, 2009)
The article attempts to succinctly underline how Nepal Rastra Bank, functioning as the Central Bank attempts to regulate the monetary policy to enhance a sound, sustainable economic development prospective for the national well-being. The daunting task towards embracing a sound monetary and fiscal policy helps to galvanize the society towards the pathway to build a sound economic development and a growth-oriented society. It uncovers the underlying objective natural factors for development strategy, as it attempts to bring forth economic acceleration, employment generation, favorable balance of payment. It puts focus on how the Central bank follows either a liberal or a rigid monetary policy in order to control the overall monetary status fine-tuning it with the ground economic realities. It harbingers overall developmental well being and prosperity of the society on health, development, education, employment generation through persuasion of a pragmatic monetary and a fiscal policy .The article points out to the challenges that if faces while undertaking to combat a sound overall development and thenceforth usher into prosperity of the society. Key words: Budget, monetary policy, Central Bank, money supply, commercial banks, economic development, fiscal policy Socio Economic Development Panorama; Vol. 1; No. 4, 2009; January-June